2019
DOI: 10.1186/s13033-019-0272-0
|View full text |Cite
|
Sign up to set email alerts
|

Health system constraints in integrating mental health services into primary healthcare in rural Uganda: perspectives of primary care providers

Abstract: Background: The World Health Organization issued recommendations to guide the process of integrating mental health services into primary healthcare. However, there has been general as well as context specific shortcomings in the implementation of these recommendations. In Uganda, mental health services are intended to be decentralized and integrated into general healthcare, but, the services are still underutilized especially in rural areas. Purpose: The purpose of this study was to explore the health systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 39 publications
1
35
0
1
Order By: Relevance
“…A-1-1-Insufficient resources: results of the analysis showed that lack of sufficient resources was the most frequent barrier regarding the provision of MH services. Findings indicated that scarcity of resources for MH services in LMICs can be classified into four main categories including restricted financial resources (12,15,33,35,39), shortage of adequate MH professionals (33)(34)(35)(38)(39)(40), insufficiency of medications (42), and limited healthcare facilities (13,33,42,43).…”
Section: A-1-resource and Administrative Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…A-1-1-Insufficient resources: results of the analysis showed that lack of sufficient resources was the most frequent barrier regarding the provision of MH services. Findings indicated that scarcity of resources for MH services in LMICs can be classified into four main categories including restricted financial resources (12,15,33,35,39), shortage of adequate MH professionals (33)(34)(35)(38)(39)(40), insufficiency of medications (42), and limited healthcare facilities (13,33,42,43).…”
Section: A-1-resource and Administrative Barriersmentioning
confidence: 99%
“…A-1-3-Centralized and non-integrated services: this review showed that one of the main barriers to equitable provision of MH services in many LMICs is that these services are usually not integrated into Primary Health Care (PHC) and a major proportion of service facilities are located in the centers of provinces (10,12,13,20,31,38,40).…”
Section: A-1-resource and Administrative Barriersmentioning
confidence: 99%
“…Many countries achieved health related goals with this approach. Low and middle income countries like Zambia, Uganda and Bangladesh integrated their mental health services with community health approach and shown massive improvement in mental health and service use (18,23,24). Preventive, promotive and rehabilitative mental health service were integrated in the Ethiopian HEP in 2015 (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The SURE Framework analysis 33 (online supplemental appendix 6) will be used to analyse data and for improving comparability and trustworthiness of the study. The SURE framework can be applied to any healthcare research 41 and the research team agreed on this framework analysis because of its domains that are linked to factors affecting health service delivery. 41 The data synthesis approach that we will use is the same approach that was used in other studies.…”
Section: Data Synthesismentioning
confidence: 99%